Flying Too Close to the Sun? Hubris Among CEOs and How to Prevent it - Petit, Valérie (Journal of business ethics, 2012)
Hubris among CEOs is generally considered to be undesirable: researchers in finance and in management have documented its unwelcome effects and the media ascribe many corporate failings to CEO hubris. However, the literature fails to provide a precise definition of CEO hubris and is mostly silent on how to prevent it. We use work on hubris in the fields of mythology, psychology, and ethics to develop a framework defining CEO hubris. Our framework describes a set of beliefs and behaviors, both psycho-pathological and unethical in nature, which characterize the problematic relationship of the hubris-infected CEO towards his or her own self, others and the world at large. We then demonstrate how the development of authentic leadership may contribute to preventing or attenuating hubris by addressing its psycho-pathological nature through the true self and meaningful relationships with others. In addition to its psycho-pathological dimension, CEO hubris also contains an ethical dimension. We therefore propose that the development of the virtue of reverence might contribute to the prevention or attenuation of CEO hubris, because reverence makes the individual aware of his or her place in the world order and membership of the community of humans.